Experimental evidence for the formation of cationic intermediates during iodine(iii)-mediated oxidative dearomatization of phenols. Issue 37 (7th September 2018) - Tang, Ting; Harned, Andrew M.
Abstract : Hammett analysis reveals iodine(iii )-mediated oxidative dearomatization reactions proceed through cationic intermediates and not direct nucleophilic attack on an activated phenol. Abstract : Iodine(iii )-based oxidants are commonly used reagents for the oxidative dearomatization of phenols. Having a better understanding of the mechanism through which these reactions proceed is important for designing new iodine(iii )-based reagents, catalysts, and reactions. We have performed a Hammett analysis of the oxidative dearomatization of substituted 4-phenylphenols. This study confirms that iodine(iii )-mediated oxidative dearomatizations likely proceed through cationic phenoxenium ions and not the direct addition of a nucleophile to an iodine-bound phenol intermediate.